Institutional racism in the child welfare system: a social justice issue - Jones, Jenny (Social work, white supremacy, and racial justice, 2023)
Federal policies that perpetuate inequities among African American families have led to the overrepresentation of Black children in the child welfare system. This chapter provides a historical overview of the antecedents that led to the development of the child welfare state that formalized racist policies that shaped the U.S. child welfare system. Embodied in this discussion is a historical account of the Black self-help/mutual aid movement that provided key aspects of Black club women’s child welfare vision that should be incorporated into contemporary child welfare policy and practice. Next, the chapter examines the impediments that African American children face within the context of racial injustice framed by Du Bois’s philosophical perspective. The chapter also provides examples of both Washington’s and Du Bois’s philosophical ideals as they relate to African Americans and the American child welfare system.